A face perversa da terceirização : a reprodução das desigualdades e dos conflitos entre os trabalhadores - Dias, Ana Patricia (2011)
This study is related to the outsourcing process within bank sector from Brazilian economy, focusing on workeforce outsourcing whose contract is the worker. It is noteworthy that this capital strategy is applied both direct and indirect approach within support and core activities. In this context, this study aimed to analyze historically how the capital through its productive improvement, such as outsourcing, led to new ways of work control in order to reproduce the worker division and keep the capitalism within Caixa Econômica Federal CEF, during 2001 and 2009. Regarding the methodological aspects, it was carried out a literature review, including the analysis of secondary data such as CEF‟s Social Report and Luta Bancária newspaper. Besides that, outsourced workers and managers were interviewed at selling place of CEF. The analysis of the outsourcing of workforce coupled with the historical study on the work category and the work social division, it was observed that contradiction of current capitalism production manner has been reproducing through the production restructuring occurred in the late twentieth century. This is because that phenomenon sets in motion preterit precarious working practices such as outsourcing, can cause further division and conflict among workers.